Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
several equations , determine (x,y)?
determine all (x, y) that are solutions to the equations.
x^2+y^2 = x-2xy+y and,
x^2-y^2=x+2xy-y
I dont understand this question (what do they even want me to do?), can someone please show me step by step. Because I want to learn.
I only know that the answers is going to be: (0.0) , (0.1) , (1,0), (1,-1)
Thank you.
4 Answers
- ted sLv 75 months ago
add then together to get 2 x² = 2x ===> x = 0 or 1....if x = 0 then y² = y ===> y = 0 or 1....if x = 1 then y² = - y ===> y = 0 or - 1 ; if x = 0 then y² = y ===> y = 0 or 1......(1,0) , ( 1 , - 1 ) and (0, 0 ) , ( (0,1 )
- la consoleLv 75 months ago
(1) : x² + y² = x - 2xy + y
(2) : x² - y² = x + 2xy - y
You calculate (1) + (2)
(x² + y²) + (x² - y²) = (x - 2xy + y) + (x + 2xy - y)
x² + y² + x² - y² = x - 2xy + y + x + 2xy - y
2x² = 2x
x² = x
x² - x = 0
x.(x - 1) = 0
First case: x = 0 → the system of the 2 equation becomes:
(1) : x² + y² = x - 2xy + y → where: x = 0 → y² = y
(2) : x² - y² = x + 2xy - y → where: x = 0 → - y² = - y → y² = y
You obtain only one equation:
y² = y
y² - y = 0
y.(y - 1) = 0
First possibility: y = 0
Second possibility: (y - 1) = 0 → y - 1 = 0 → y = 1
2 solutions (x ; y) → (0 ; 0) (0 ; 1)
Second case: (x - 1) = 0 → x - 1 = 0 → x = 1 → the system of the 2 equation becomes:
(1) : x² + y² = x - 2xy + y → where: x = 1 → 1 + y² = 1 - 2y + y → y² = - y
(2) : x² - y² = x + 2xy - y → where: x = 1 → 1 - y² = 1 + 2y - y → - y² = y → y² = - y
You obtain only one equation:
y² = - y
y² + y = 0
y.(y + 1) = 0
First possibility: y = 0
Second possibility: (y + 1) = 0 → y + 1 = 0 → y = - 1
2 solutions (x ; y) → (1 ; 0) (1 ; - 1)
Resume the solutions (x ; y)
(0 ; 0) (0 ; 1) (1 ; 0) (1 ; - 1)
- ?Lv 75 months ago
Rewrite the first eqs as x² + 2xy + y² = x+y --> (x+y)² = x+y.
Two cases: x+y=0 thus x=-y, OR x+y = 1 thus x = 1-y.
Replace each of these into the other eqs. Your solutions will follow.
Done!
- llafferLv 75 months ago
This is a system of two equations and two unknowns:
x² + y² = x - 2xy + y and x² - y² = x + 2xy - y
Let's solve the first equation for y in terms of x. First, I'll move everything to one side then group the like-terms together to make a quadratic. Any term with only "x" in it will be considered a constant for now:
x² + y² - x + 2xy - y = 0
y² + 2xy - y + x² - x = 0
y² + (2x - 1)y + (x² - x) = 0
Now we have a quadratic where:
a = 1
b = 2x - 1
c = x² - x
Quadratic equation:
y = [ -b ± √(b² - 4ac)] / (2a)
y = [ -(2x - 1) ± √((2x - 1)² - 4(1)(x² - x))] / (2 * 1)
y = [ -2x + 1 ± √(4x² - 4x + 1 - 4(x² - x))] / 2
y = [ -2x + 1 ± √(4x² - 4x + 1 - 4x² + 4x)] / 2
The x and x² terms cancel out under the square root:
y = [ -2x + 1 ± √(1)] / 2
y = (-2x + 1 ± 1) / 2
y = (-2x + 1 - 1) / 2 and y = (-2x + 1 + 1) / 2
y = -2x / 2 and y = (-2x + 2) / 2
y = -x and y = -x + 1
Now we have two expressions for y in terms of x. If we substitute them into the other equation we will have two additional quadratics to solve:
x² - y² = x + 2xy - y
x² - (-x)² = x + 2x(-x) - (-x) and x² - (-x + 1)² = x + 2x(-x + 1) - (-x + 1)
x² - x² = x - 2x² + x and x² - (x² - 2x + 1) = x + (-2)x² + 2x + x - 1
0 = -2x² + 2x and x² - x² + 2x - 1 = -2x² + 4x - 1
0 = -x² + x and 2x - 1 = -2x² + 4x - 1
0 = -x² + x and 0 = -2x² + 2x
0 = -x² + x and 0 = -x² + x
Now that both equations are the same, we can solve one to get solutions for both:
0 = -x² + x
0 = (-x + 1)x
-x + 1 = 0 and x = 0
1 = x and x = 0
Now that we have two values for x we'll put them into both expressions for y to see what we end up with:
y = -x and y = -x + 1
y = -0 and y = -0 + 1 and y = -1 and y = -1 + 1
y = 0 and y = 0 + 1 and y = -1 and y = 0
y = 0 and y = 1 and y = -1 and y = 0
When x = 0 we have y = 0 and 1. That gives us the two points (0, 0) and (0, 1).
When x = 1 we have y = -1 and 0. That gives us the two points (1, -1) and (-1, 0).
All four points are a solution to the system of equations.